Direct Radiotherapy-Induced Effects on Dental Hard Tissue in Combination With Bleaching Procedure - Klarić Sever, Eva; Tarle, Andro; Soče, Majana; Grego, Timor (Frontiers in Dental Medicine, 2021)
The aim of this study was to evaluate the effects of radiation and tooth bleaching on the physical and morphological properties of enamel and dentin on permanent teeth. Eighty fresh, non-carious third molars were used in this study. Before cutting the crown in half, the teeth samples were randomly allocated to treatment and control groups by using a lottery method. The first group (n=20) underwent standard radiation protocol (2 Gy/fraction/day, 5 days/week) with afterward bleaching treatment using 16 % carbamide peroxide gel, second group (n=20) underwent standard radiation protocol with afterward bleaching treatment using 38 % hydrogen peroxide, third group (n=20) underwent a short, one strong, experimental dose of 70 Gy with afterward bleaching treatment using 16 % carbamide peroxide gel, fourth group (n=20) underwent one strong, experimental dose of 70 Gy with afterward bleaching treatment using 38 % hydrogen peroxide gel. Groups 5-8 (n=20) served as control as they underwent only bleaching treatment. Vickers microhardness and surface roughness were performed before (initial), after irradiation and bleaching or after only bleaching. The effects of irradiation and bleaching on microhardness (or roughness) of enamel and dentin were analyzed in repeated measures ANOVA model. Enamel microhardness after experimental single 70 Gy irradiation or after standard radiation protocol and bleaching with 16% or 38 % gel was not statistically significant from microhardness in the control group (p>0.05). There was statistically significantly greater reduction in the average microhardness of enamel and dentin during bleaching with 38% gel compared to 16% for both radiation protocols (p <0.001). After experimental 70 Gy irradiation and bleaching with 16% statistically significant increase in surface roughness was found for enamel (p=0.006) and dentin (p=0.018) while this was not recorded for 38% gel. There was statistically significantly greater increase in the average roughness of enamel and dentin during bleaching with 38% gel compared to 16% (p <0.001) for both radiation protocols. Directly induced radiation leads to potential damage of hard dental tissues, which can be further damaged by an additional bleaching. If teeth whitening is necessary after irradiation, it is suggested to use lower concentrations of whitening gels.